Religionsunterricht unter pluralistischen Voraussetzungen: Grundlagen und Grundfragen - Härle, Wilfried (Zeitschrift für Theologie und Kirche, 2020)
Today's fundamental questions about religious education in schools almost all have to do with how to determine appropriate relationships - especially between religious communities and the state, but also among the communities themselves, our pluralistic society and the competing principles of the various faiths, as well as between religious education as a staple of the curriculum and possible alternative lessons. Renewed reflection on the religious and constitutional foundations of religious education reveals a remarkable array of opportunities for orientating these relationships with regard to both the law and the Protestant church. In an elementary way, much of this can be summed up in the formula coined by Martin Heckel: »Cooperation, yes - fusion, no.« But cooperation is only possible with partners who meet the necessary requirements.